Peran Manajemen Kemasyarakatan Dalam Usaha Pengembangan Madrasah Ibtidaiyah Swasta - Hanif Hanani; Giyoto Giyoto; Yusuf Rohmadi (ITB AAS INDONESIA Surakarta, 2021)
The role of madrasas as models of Islamic education today is growing quite rapidly. It has even become an alternative institution for some Muslim families in educating their children. This is because madrasas are considered to provide two dimensions of Muslim scientific life between worldly and hereafter needs. Community participation in education development is an important issue in the National Education System Law no. 20 of 2003, a policy that involved the community in education programs and the birth of a school-based management (SBM) offer that gave relatively broad autonomy to schools and communities. In Chapter III article 8 it is stated that